Rancang Bangun Pelaporan Kerusakan Sarana Dan Prasarana Di Sma Negeri 1 Kasongan Berbasis Website - Meyland, Helinda; Oktaviyani, Enny Dwi; Parhusip, Jadiaman (Universitas Palangka Raya, 2023)
The use of facilities and infrastructure is very important for the continuity of the teaching and learning process and for improving the quality of learning for both students and teachers. Facilities and infrastructure greatly affect the ability of students to learn. This shows that the role of facilities and infrastructure is very important in supporting the quality of student learning. Managing facilities and infrastructure is a very important activity in schools, since its existence will greatly support the success of the learning process in schools. So it is necessary to have a system that is able to handle this, which makes website-based Design and Build Facility and Infrastructure Damage Reporting able to run quickly, precisely and the data manage is valid. Because of the problems above, an innovation was created to create a website-based application that can be accessed by the school, in order to monitor the management and maintenance of facilities and infrastructure in schools. The realization of this system requires an observation at SMA Negeri 1 Kasongan to get the real process and the data needed to form an information system. Software development involves the Waterfall method with multiple steps, including needs analysis, system design, implementation, integration and testing, and operation and maintenance. By implementing the waterfall method in designing and building reporting of damage to facilities and infrastructure at SMA Negeri 1 Kasongan, the system will assist the school in processing information regarding reporting of damaged facilities and infrastructure and simplify the process of submitting school improvements to the Provincial Education Office.